Theoretical examination of the fracture behavior of BC3 polycrystalline nanosheets: Effect of crack size and temperature. (February 2022) - Dadrasi, Ali; Albooyeh, Alireza; Fooladpanjeh, Sasan; Salmankhani, Azam; Hamed Mashhadzadeh, Amin; Saeb, Mohammad Reza
Abstract: 2D carbon graphene nanostructures are elements of advanced materials and systems. This theoretical survey provides explanation to the mechanical and fracture behavior of mono- and polycrystalline BC3 nanosheets (denoted as MC- and PCBC3 NS, respectively) as a function of temperature and the type of crack defects. The mechanical performance of PCBC3 NS at elevated temperatures was monitored varying the number of grain boundaries (the main source of stress concentration) by considering structural defects forming during the crystal growth. Molecular dynamics (MD) simulation was applied as a cost-effective technique to model and test MC- and PCBC3 NS by selecting the proper potential function and boundary conditions. The results demonstrated that the mechanical properties of the perfect crystalline PCBC3NS was decreased by increase of the number of grains, particularly when the grain numbers were equal to or more than 36. For defective PCBC3 NS, the mechanical properties were decreased by the crack length and the temperature. The lowest values of the Young's modulus, failure stress, and failure strain were assigned to the PCBC3 NS having the crack length of L/2 at 1000 K, respectively by 23%, 46%, and 33% lower than the corresponding defect-free PCBC3 NS. The crack tip played a key role in failure behavior, even more that the number of grain boundaries. Eventually, the critical stress intensity was decreased gradually by increasing the temperature. The results of this work can be generalized to more complicated cases to deepen understanding and predict fracture fingerprint of the next generations of 2D nanostructures. Highlights: Mechanical properties of random polycrystalline BC3 nanosheets were theoretically studied. Effect of grain number on the Young's modulus, failure stress, and failure strain was reported. By increasing the grain number, the studied mechanical properties reached constant values. Fracture mechanism was considered with for grain number 36 and different crack lengths. Stress intensity factor fell by 40% by temperature rise from 100 K to 1000 K for crack L/3.